Exploring Leadership Styles to Navigate Organizational Resilience in COVID-19: A Qualitative Inquiry into Thai Startups - Udharasawasdi, Seri; Petchsawang, Pawinee (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study explores how leadership styles contribute to organizational resilience among Thai startups during the COVID-19 pandemic. The study employed a multiple-case study approach, conducting semi-structured interviews with three startup CEOs and analyzing the data through thematic categorization to identify patterns and commonalities across cases. The findings reveal five themes: fostering strategic adaptation and organizational agility for business growth, promoting employee growth and empowerment, creating a flexible work environment, driving strategic communication, and customer-centricity. These five themes fit into six existing leadership styles: charismatic leadership, transformational leadership, servant leadership, adaptive leadership, mindful leadership, and entrepreneurial leadership. This study advances leadership and organizational resilience literature by illustrating how integrating multiple leadership styles—charismatic, transformational, servant, adaptive, mindful, and entrepreneurial—fosters proactive resilience in volatile environments like the COVID-19 pandemic. Practically, it offers startups actionable insights for embedding resilience into culture, aligning HR strategies with adaptability, and cultivating leadership capabilities essential for sustaining growth amid uncertainty.